Keterbatasan Koleksi Literasi Islam dalam Pemenuhan Informasi Bidang Studi Islam di Perpustakaan Pondok Pesantren Darul Ulum Tigo Jangko Lintau Buo - Dodi Nofri Yoliadi (IAIN Batusangkar, 2022)
The focus of this research is the limited collection of Islamic literacy in fulfilling information in the field of Islamic studies in the Darul Ulum Islamic Boarding School library Tigo Jangko Lintau Buo. The purpose of this study was to determine the level of user satisfaction with the provision of Islamic book collections and to determine the suitability of existing Islamic book collections with the information needs of users at the Darul Ulum Tigo Jangko Lintau Buo Islamic Boarding School Library. The method used is descriptive qualitative, librarians and librarians of the Darul Ulum Islamic Boarding School Library Tigo Jangko Lintau Buo are informants in this study. The data collection techniques used in this research include observation, interviews and documentation. Then the data obtained were analyzed using Miles and Huberman data analysis. The results of this study found that the students of the Darul Ulum Islamic Boarding School Tigo Jangko Lintau Buo had a low level of satisfaction with the collection of Islamic books served in the library because the information obtained was insufficient to meet the information needs expected by users.